Go as a River - Read, Shelley (New York : Spiegel and Grau, 2023)
"Seventeen-year-old Victoria Nash runs the household on her family's peach farm in the small ranch town of Iola, Colorado--the sole surviving female in a family of troubled men. Wilson Moon is a young drifter with a mysterious past, displaced from his tribal land and determined to live as he chooses. Victoria encounters Wil by chance on a street corner, a meeting that profoundly alters both of their young lives, unknowingly igniting as much passion as danger. When tragedy strikes, Victoria leaves the only life she has ever known. She flees into the surrounding mountains where she struggles to survive in the wilderness with no clear notion of what her future will bring. As the seasons change, she also charts the changes in herself, finding in the beautiful but harsh landscape the meaning and strength to move forward and rebuild all that she has lost, even as the Gunnison River threatens to submerge her homeland--its ranches, farms, and the beloved peach orchard that has been in her family for generations. Inspired by true events surrounding the destruction of the town of Iola in the 1960s, Go as a River is a story of deeply held love in the face of hardship and loss, but also of finding courage, resilience, friendship, and, finally, home--where least expected. This stunning debut explores what it means to lead your life as if it were a river--gathering and flowing, finding a way forward even when a river is dammed."--Provided by publisher.
Keywords: Families -- Fiction; Bildungsromans; Romance fiction; Novels